From Ritual to Revenue: Reframing Indonesia Pilgrimage Management as A Strategic Economic Diplomacy - Majid, Marenda; Azhaar, Aisyah Nabilah; Nurdiana, NDR Ayu; Febriana, Zakiyya Nisa; Febriana, Affifah Nisa (Jurnal Ilmiah Teunuleh, 2025)
This research analyzes Indonesia's pilgrimage administration from the perspective of strategic economic diplomacy. Indonesia, the most populous Muslim-majority nation, holds a distinctive role in the global pilgrimage sphere, administering the highest yearly Hajj quota. The Hajj, though a religious duty, is administered in Indonesia in a manner that extends beyond spiritual aspects, intertwining with economic, political, and diplomatic considerations. This research employs a descriptive-qualitative methodology, utilizing Miles and Huberman's analysis, to investigate the evolution of pilgrimage services into a substantial economic sector that creates employment, invigorates regional economies, and promotes bilateral collaboration. The Hajj Financial Management Agency (BPKH) is pivotal in directing substantial religious donations into national development initiatives. Nonetheless, intersecting restrictions, operational inefficiencies, and ethical dilemmas expose systemic constraints. The results underscore how Hajj governance embodies Indonesia's overarching diplomatic aspirations, especially in utilizing religio-cultural capital for foreign policy and economic strategy. This research enhances scholarship by reconceptualizing Hajj management as a tool of economic diplomacy rather than simply a logistical-religious duty. It emphasizes the necessity for open, ethical, and innovative governance to augment Indonesia’s soft power while guaranteeing equitable and spiritually enriching pilgrimage experiences.